Energy model for propeller-powered aircraft hybrid propulsion system - Gomes, Ivandro do Espírito Santo Bragança (2021)
In order to respond to a highly demanding industry, the search for new systems of propulsion is increasingly intense due to the environmental impact as well as the performance of such systems. This work aims to explore several flight and work conditions of a hybrid propulsion system in a propeller-powered aircraft by developing a program that simulates the system. Hybrid propulsion systems can be classified into five categories: series, parallel, seriesparallel, complex and fuel cell. In this work the series, parallel, parallel decoupled and parallel coupled configuration are analyzed. By modelling and analyzing how the subsystems work individually and how they perform together, it is possible to analyze the performance of the hybrid system. To make this application the software used for the programming was the compiler JetBrains PyCharm Community Edition and the language used was Python. Implementing subsystem models with functions and Python loop, the code simulates the performance. Since the amount of output data is large (from each subsystem), the program shows graphs, and it will automatically create a file with the data so that the user can compare with other configurations or other specifications of the models. For this work, three out of four configurations were simulated: series, coupled with two propeller and coupled with one propeller. By comparing the performance of the systems under the same flight condition, i.e., altitude and velocity, allows to perceive how each configuration works. Being able to compare different configurations allows the user to identify, for example, the system that consume less, the subsystems that can be downsized (like the motor or the engine) or the system that has the higher endurance.